Tingkat Kereligiusan Siswa SMA/SMK di Kota Dan Desa - Rizky Nur Pratama; Sri Khaerunnisa; Qurrotul Aini; Basrowi Basrowi (Jurnal Kajian Pendidikan Islam, 2022)
The level of religiosity of SMA/SMK students is fading day by day due to an unsupportive lifestyle and social environment. The purpose of this study is to describe strategies to increase student religiosity in schools. The study used qualitative methods, by conducting participatory observations and in-depth interviews. Based on the results of data analysis, it can be seen that methods that are able to change the character of students to become religious include: 1) providing related sanctions or punishments that can change the character of these students, 2) applying 5S (Smile, Greetings, Greetings, Polite). and Courtesy) in the school environment and apply it in the community. 3) reading the Koran after participating in IMTAQ extracurricular, respecting others in shaping the personality of students, creating a conducive environment for growing faith and piety of students through habituation and moral development of students through religious activities in schools so that they can be applied in schools. outside the school environment.